A Favorable Treatment Outcome in RANBP2 and Influenza Associated Acute Necrotizing Encephalitis. (December 2022) - Galan, Fernando; Nordli, Douglas R.; Yazdani, Milad; Klein, Jessica
In current literature, there is uncertainty in the pathophysiology and management of influenza-associated Acute Necrotizing Encephalitis. Because of this and the rarity of the disease, no clear treatment guidelines exist. It is thought that treatment after 24 h of symptom onset or known brainstem involvement are poor predictors of outcome. Here, we present a case that provides support for aggressive management of the inflammatory cascade with combination high-dose steroid, immunoglobulin, and anti-viral therapy with oseltamivir despite initiation after 24 h from symptom onset, brainstem involvement, and a pathogenic RANBP2 gene mutation which mechanistically increases oxidative stress, cytokine effects, and possibly viral invasion into brain tissue and vasculature.